2017
DOI: 10.1021/acsomega.7b01490
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Effects on the Structural Flexibility of Phosphoglucosamine Mutase from Bacillus anthracis

Abstract: Phosphoglucosamine mutase (PNGM) is an evolutionarily conserved bacterial enzyme in the peptidoglycan biosynthetic pathway, catalyzing the reversible conversion between glucosamine 1- and 6-phosphate. Previous structural studies of PNGM from the pathogen Bacillus anthracis revealed its dimeric assembly and highlighted the rotational mobility of its C-terminal domain. Recent studies of two other enzymes in the same superfamily have demonstrated the long-range effects on the conformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…Also as part of this study, we characterized a series of “off pathway” complexes of XcPGM. These include E deP with a bound substrate or product (states 8–11 on Table I) as well as an E P :I complex (state 14 ) also previously determined 3 . None of these are part of the productive catalytic cycle, but may occur, for example, if the enzyme binds the ligand after losing its phosphoryl group from hydrolysis.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Also as part of this study, we characterized a series of “off pathway” complexes of XcPGM. These include E deP with a bound substrate or product (states 8–11 on Table I) as well as an E P :I complex (state 14 ) also previously determined 3 . None of these are part of the productive catalytic cycle, but may occur, for example, if the enzyme binds the ligand after losing its phosphoryl group from hydrolysis.…”
Section: Resultsmentioning
confidence: 93%
“…1(a)]. As noted above, hydrogen-deuterium exchange by mass spectrometry, NMR, and various biochemical studies of other enzymes in the superfamily has suggested that E deP has increased flexibility of its polypeptide backbone relative to E P. 8,9,11,18 These flexibility changes, which have not been apparent in crystal structures, have been proposed to facilitate the release and reorientation of G16P 9,11 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In other members of the superfamily, similar biochemical evidence is mounting for phosphorylation- dependent differences in protein flexibility (Y. Lee, Stiers, et al, 2014; Stiers, Xu, Lee, & Beamer, n.d.), suggesting that this is a conserved feature of the PHMs, and supporting its functional importance in enzyme mechanism.…”
Section: Catalytic Mechanismmentioning
confidence: 79%